An individual claims history simulation machine - Andrea Gabrielli; Mario V. Wüthrich (Risks, 2018)
The aim of this project is to develop a stochastic simulation machine that generates individual claims histories of non-life insurance claims. This simulation machine is based on neural networks to incorporate individual claims feature information. We provide a fully calibrated stochastic scenario generator that is based on real non-life insurance data. This stochastic simulation machine allows everyone to simulate their own synthetic insurance portfolio of individual claims histories and back-test thier preferred claims reserving method.
Keywords: 330; claims reserving; individual claims; claims cash flows; micro-level stochastic reserving; loss reserving; claims simulation; neural network reserving; individual claims features; individual claims covariates; chain-ladder